Simulation of terminal and logistics processes of foreign trade cargo processing at the Grodekovo border station - R. G. Korol’; O. N. Chislov (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. The transport and logistics business has undergone significant changes while overcoming the challenges facing the transport industry. It requires new approaches to rational use, as well as the introduction of innovative technologies in the organisation of foreign trade transportation. This issue is especially relevant in the Far East region, where there is an imbalance of incoming freight flows and traffic capacity of the transport network, which leads to a decrease in the quality of transport services and the competitiveness of transport corridors running through Russia. The key elements of international transport corridors are transport hubs and border checkpoints; therefore, the purpose of the study is to assess the workload of a railway cargo terminal of the Pogranichny checkpoint within the Primorye-1 transport corridor. The object of study is the terminal and logistics complex of the Grodekovo border station.Materials and methods. In this study, methods of system analysis and information synthesis were used, as well as a programme for simulating the operation of technological zones of a border terminal and logistics centre.Results. The developed simulation programme made it possible to assess the workload of the warehouse terminal of the Grodekovo border station for processing foreign trade freight flow arriving by rail and road from Heilongjiang Province (PRC). The article presents the results of simulation modelling.Discussion and conclusion. Analysis of the results of simulation modelling showed the functioning of the cargo terminal of the Grodekovo border station with an increase in freight flow coming by road for reloading onto railway rolling stock, taking into account the duration of customs clearance, the limited capacity of the storage area and the cargo front, the number of handling equipment. Further research is aimed at creating a comprehensive programme that takes into account the traffic capacity of the entire system of ground checkpoints in the Far East region and the volume of the predicted freight flow.